2002
DOI: 10.1128/jvi.76.18.9481-9492.2002
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Wild-Type Virus and Lack of Temporal Structure in the Latent Reservoir for Human Immunodeficiency Virus Type 1 in Pediatric Patients with Extensive Antiretroviral Exposure

Abstract: Although highly active antiretroviral therapy (HAART) for human immunodeficiency virus type 1 (HIV-1) infection can reduce levels of HIV-1 RNA in plasma to below the limit of detection, replication-competent forms of the virus persist in all infected individuals. One form of persistence involves a stable reservoir of latent but potentially infectious virus that resides in resting memory CD4 ؉ T cells. The mechanisms involved in maintaining this latent reservoir are incompletely understood. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 40 publications
(63 reference statements)
9
117
0
Order By: Relevance
“…Phylogenetic analysis suggests that the M184V variants evolved recently, most likely as a result of entecavir treatment. The appearance of M184V could also reflect emergence of an archived variant from the latent reservoir (26), but in either case there is clear evidence that entecavir selected for this variant in patient #1.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis suggests that the M184V variants evolved recently, most likely as a result of entecavir treatment. The appearance of M184V could also reflect emergence of an archived variant from the latent reservoir (26), but in either case there is clear evidence that entecavir selected for this variant in patient #1.…”
Section: Discussionmentioning
confidence: 99%
“…In the chronic infection phase, there is a slow but perceptible turnover of the viral population such that genetically distinct populations arise every few years (F Maldarelli, M Kearney, S Palmer, et al, unpubl.). In contrast, in patients on maximally suppressive therapy, evolution of viral genomes is frozen at the point at which therapy began (Ruff et al 2002;Tobin et al 2005), and no evidence for continuing evolution can be seen even after many years. In patients for which therapy is partially suppressive, ongoing evolution can still be observed (Tobin et al 2005), as is also true in patients known as "elite controllers," who naturally control HIV-1 infection at levels similar to those seen in patients on suppressive antiviral therapy (Mens et al 2010).…”
Section: Persistence Of Hiv-1 Infection On Therapymentioning
confidence: 99%
“…6 Genetic studies have shown drug-sensitive archival HIV-1 sequences can be found in T cells in patients who have undergone antiretroviral therapy for up to 5 years. 7 Longitudinal studies in patients undergoing antiretroviral therapy for 2 years found a lack of clinically relevant evolution in the protease gene in HIV recovered from peripheral blood cells. 8 The virus was replication competent but apparently had not been exposed to the selection pressure exerted by the therapy, implying that the virus was not replicating.…”
Section: Introductionmentioning
confidence: 99%